2020
DOI: 10.1111/mec.15419
|View full text |Cite
|
Sign up to set email alerts
|

Paternally‐biased gene expression follows kin‐selected predictions in female honey bee embryos

Abstract: In contrast, the reproductive interests of a mother are generally favoured if her maternal resources are partitioned equally among her present and future offspring. This means that the reproductive interests of mothers and fathers are sometimes in conflict (Burt & Trivers, 2006). Therefore, selection can act divergently on fathers and mothers so that they modify certain genes in their offspring in ways that favour their offspring's reproductive success. Since "imprinting" often implies epigenetic mechanisms li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 57 publications
2
32
0
Order By: Relevance
“…Experimental designs using reciprocal crosses may avoid these issues because they directly target differences in RNA-sequences, rather than comparing RNA-sequences to DNA-sequences as we did (e.g. Galbraith et al, 2016;Kocher et al, 2015;Smith et al, 2020), but we cannot necessarily assume they are immune to duplicated gene complications. Because reciprocal crosses imply that putatively imprinted genes are expressed in different cytoplasmatic backgrounds, this design would also be liable to unexpected expression patterns should the target gene be present in two copies.…”
Section: Application To Acromyrmex Echinatiormentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental designs using reciprocal crosses may avoid these issues because they directly target differences in RNA-sequences, rather than comparing RNA-sequences to DNA-sequences as we did (e.g. Galbraith et al, 2016;Kocher et al, 2015;Smith et al, 2020), but we cannot necessarily assume they are immune to duplicated gene complications. Because reciprocal crosses imply that putatively imprinted genes are expressed in different cytoplasmatic backgrounds, this design would also be liable to unexpected expression patterns should the target gene be present in two copies.…”
Section: Application To Acromyrmex Echinatiormentioning
confidence: 99%
“…Often, genomic imprinting is observed as complete silencing of one allele and expression exclusively from the other, but imprinted genes that show only an incomplete bias are increasingly being found (e.g. Galbraith et al., 2016; Smith et al., 2020). Although there are a number of theories that propose explanations for the evolution of imprinting (reviewed in Haig, 2014; Spencer & Clark, 2014), the best supported of these—the kinship theory of genomic imprinting—posits that genomic imprinting arises because of conflict between maternally and paternally inherited alleles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Utilizing a cross between European (Apis mellifera ligustica ) and Africanized honey bees, Galbraith et al 2016 identified genes exhibiting a pattern of biased paternal allele overexpression in worker reproductive tissue from colonies that were queenless and broodless, a colony condition that promotes worker reproduction [9]. Smith et al 2020 found a similar pattern of paternal allele overexpression in diploid (worker-destined) eggs in a cross between two African subspecies, A.m. scutellate and A.m. capensis [10]. In reciprocal crosses of European ( A.m. ligustica and A.m. carnica ) and Africanized honey bees reared in colonies containing both brood and a queen, Kocher et al 2015 instead found parent-of-origin effects in gene expression that were largely overexpressing the maternal allele in both directions of the cross [11].…”
Section: Introductionmentioning
confidence: 99%
“…This problem is immediately apparent upon viewing the alignments in a genome browser and almost impossible to notice otherwise. Because researchers have lacked convenient ways to visualize their data, many studies have overlooked this not-well-known aspect of spliced alignment tools [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%